Letter (copy) - McDonald, Florence
042-0106-001 FEM/MT/75 Secretary's 4th October, 1937. Sir Daniel Stevenson, Bart., LL.D., Scottish Ambulance Unit in Spain, 5 Cleveden Road, GLASGOW, W.2. Dear Sir, I am writing to thank you for your letter of 1st October, as Sir Walter Citrine is at present in Bournemouth attending the Labour Party Conference. Upon his return to the office, your letter regarding the Ambulance Unit in Spain will be shown to him. Yours faithfully, Private Secretary. 292/946/42/106